Cardiac Troponin and Recurrent Major Vascular Events after Minor Stroke or Transient Ischemic Attack. Issue 6 (11th October 2021) - Hellwig, Simon; Ihl, Thomas; Ganeshan, Ramanan; Laumeier, Inga; Ahmadi, Michael; Steinicke, Maureen; Weber, Joachim E.; Endres, Matthias; Audebert, Heinrich J.; Scheitz, Jan F.
Abstract : Objective: This study was undertaken to investigate whether high‐sensitivity cardiac troponin T (hs‐cTnT) is associated with major adverse cardiovascular events (MACE) in patients with minor stroke or transient ischemic attack (TIA), and whether this association differs after risk stratification based on the Age, Blood Pressure, Clinical Features, Duration of Symptoms, Diabetes (ABCD 2 ) score. Methods: INSPiRE‐TMS was a randomized controlled trial allocating patients with minor stroke or TIA to an intensified support program or conventional care. In this post hoc analysis, participants were categorized using hs‐cTnT levels (5th generation; Roche Diagnostics, Manheim, Germany; 99th percentile upper reference limit [URL] = 14ng/l). Vascular risk was stratified using the ABCD 2 score (lower risk = 0–5 vs higher risk = 6–7). Cox proportional hazard regression was performed using covariate adjustment and propensity score matching (PSM) for the association between hs‐cTnT and MACE (stroke/nonfatal coronary event/vascular death). Results: Among 889 patients (mean age = 70 years, 37% female), MACE occurred in 153 patients (17.2%) during a mean follow‐up of 3.2 years. hs‐cTnT was associated with MACE (9.3%/yr, >URL vs 4.4%/yr, ≤URL, adjusted hazard ratio [HR] = 1.63 [95% confidence interval (CI) = 1.13–2.35], adjusted HR [Q4 vs Q1 ] = 2.57 [95% CI = 1.35–4.97], adjusted HR [log‐transformed] = 2.31 [95% CI = 1.37–3.89]). This association remained after PSM (adjusted HR = 1.76 [95% CI = 1.14–2.72]). There was a significant interaction between hs‐cTnT and ABCD 2 category for MACE occurrence ( p interaction = 0.04). In the lower risk category, MACE rate was 9.5%/yr in patients with hs‐cTnT > URL, which was higher than in those ≤URL (3.8%/yr) and similar to the overall rate in the higher risk category. Interpretation: hs‐cTnT levels are associated with incident MACE within 3 years after minor stroke or TIA and may help to identify high‐risk individuals otherwise deemed at lower risk based on the ABCD 2 score. If confirmed in independent validation studies, this might warrant intensified secondary prevention measures and cardiac diagnostics in stroke patients with elevated hs‐cTnT. ANN NEUROL 2021;90:901–912